Strengthening regional identity establishing the sense of place of Northern Mindanao for the redevelopment of Laguindingan International Airport - Valencia, Lawrence Yancy R. (2019)
Airports serve as cultural gateways to destinations. Most often, these are designed without the reflection of the destination?s identity or consideration of human experience. The research aimed to address this problem by studying the commodified relationship of the users to the existing Laguindingan International Airport by matching user satisfaction and expected service (level of importance), as well as the perception of tourists and locals to Region X: Northern Mindanao. Based on the Traveler Opinion and Satisfaction Survey, travelers view accessibility and functionality as the most important airport attributes, while reflecting relatively small satisfaction score, yielding a relatively low commodified relationship. The sense of place of the region was measured using a psychometric survey developed by Suzanne Bott. The results from the survey, together with the assessment of the commodified relationship of the users with the airport, agreed that the region?s identity relied mostly on its natural features (mountains, pineapple plantations, and cold climate), warmth and inclusivity of the community, and their cultural icons and activities (ethnolinguistic tribes and festivals). Even though the region is known and remembered mainly because of these aspects, it was revealed that it has a weak sense of place. Through amplifying these aspects, the region will most likely leave a better and long-lasting mark for its residents and tourists.